Students’ and tutors’ perceptions of feedback on academic essays in an open and distance learning context - Jack Matlou Chokwe (Open Praxis, 2015)
Feedback is the most important aspect of the learning and teaching process. Through feedback, tutors/lecturers provide an important intervention in teaching as students would always like to know where they did right or wrong in their written assessed work. Without feedback, learning is not complete. This article reports on the results of a major study on academic writing of first year English Second Language university students in open and distance learning context. The study probed both students’ perceptions and tutors’ practices in the provision of giving feedback. Marked students’ assignments were evaluated using document analysis method and interviews were held with students and tutors. The findings show that feedback provided to students is not always sufficient and therefore denying students’ opportunities to learn effectively as they would not know their weak and strong points.